Knowledge of NFRS among Accounting Faculties of Universities in Nepal - Upadhyay, Jitendra Prasad; Adhikari, Pitri Raj (NCC Journal, 2024)
This study aims to investigate the knowledge of NFRS among the accounting faculties of universities in Nepal. Four different issues related to NFRS i.e. accounting treatment, provision for implementing NFRS, familiar with the major constraints for implementing NFRS, and need of training for implementing have been used in this study as the determinant's performance. Data were collected with a structured questionnaire survey from 50 accounting faculties of different universities. The collected data were analyzed and the findings revealed that accounting faculties of universities in Nepal have not enough knowledge about NFRS and they need training regarding NFRS.